2007
DOI: 10.1037/1524-9220.8.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Conformity to masculine norms, Asian values, coping strategies, peer group influences and substance use among Asian American men.

Abstract: This study explores the relationship between Asian values (AVS-R; Kim & Hong, 2004), Conformity to Masculine Norms Inventory (CMNI;Mahalik et al., 2003), Peer Substance Use, Coping Styles (Carver, 1997), and Substance Use among 154 Asian American college men. Results showed 47.9% reported consuming alcohol; 27% reported binge drinking; 8% used illicit drugs; 18% reported marijuana use; and 3% indicated cocaine use in the 30 days prior to completing the survey. Peer drug use was significant and the most robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
175
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(197 citation statements)
references
References 63 publications
15
175
1
2
Order By: Relevance
“…The participants were given both the CFNI-45 (Parent & Moradi, 2010) These results indicate that female athletes conform to traditional masculine norms that are associated with participation in sports. In relation to the outcomes of body esteem, the authors note that although the masculine norm Risk-taking has been associated with negative outcomes including higher levels of alcohol use (Liu & Iwamoto, 2007), this norm was linked to a positive outcome -higher levels of body esteem -among the women in this sample. This may indicate how masculine norms operate differently for women in certain domains such as sports.…”
Section: Gender As Multidimensionalmentioning
confidence: 98%
See 1 more Smart Citation
“…The participants were given both the CFNI-45 (Parent & Moradi, 2010) These results indicate that female athletes conform to traditional masculine norms that are associated with participation in sports. In relation to the outcomes of body esteem, the authors note that although the masculine norm Risk-taking has been associated with negative outcomes including higher levels of alcohol use (Liu & Iwamoto, 2007), this norm was linked to a positive outcome -higher levels of body esteem -among the women in this sample. This may indicate how masculine norms operate differently for women in certain domains such as sports.…”
Section: Gender As Multidimensionalmentioning
confidence: 98%
“…Indeed, it has been noted that the masculine norm of risktaking in particular is associated with a number of negative outcomes including excessive alcohol use (Liu & Iwamoto, 2007), as both risk-taking and alcohol use reflect traditional, hegemonic notions of masculinity (Mahalik et al, 2003). Perhaps women who strive to move away from traditional notions of femininity by instead endorsing notions of masculinity, may value risk-taking as a reflection of masculinity, which in turn confers risk for heavier drinking.…”
Section: Data Analytic Planmentioning
confidence: 99%
“…This concerned the studies by Brain et al [19] As shown in Table 1, only one study reported that the turning to religion items did not fit onto the proposed factor structure [22]. Five studies [16,[40][41][42][43] reported that items from the religious coping sub-scale loaded together with items from other sub-scales. For four of these studies, both turning to religion items loaded onto the same factor, whereas in Zelikovsky et al [16] only one item loaded with another factor, while the other item was excluded due to a factor loading below 0.40.…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
“…All five studies conducted a PCA. Three of these [16,40,41] used an orthogonal (varimax) rotation, one [42] an oblique (direct oblimin) rotation, and one study [43] did not specify the rotation method. Apart from the study by Lee and Liu [41], who had a sample size of 406 using university undergraduate students, the sample sizes of the other four studies were very similar, ranging from 104 to 154.…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
“…In the past 5 years, the CMNI-94 has been used in a number of studies with the subscales demonstrating small to moderate associations with a variety of issues such as relationship functioning, psychological distress, alcohol consumption, coping styles, and vocational interests (e.g., Burn & Ward, 2005;Liu & Iwamoto, 2007;Mahalik, Levi-Minzi, & Walker, 2007;Mahalik, Perry, CoonertyFemiano, Catraio, & Land, 2006;Mahalik & Rochlen, 2006). These studies highlight the importance of understanding the connections between gender socialization and relational, psychological, and vocational functioning.…”
mentioning
confidence: 99%